2022
DOI: 10.1002/advs.202202933
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Germanene Nanosheets as an Antioxidative Defense Agent for Acute Kidney Injury Treatment

Abstract: Acute kidney injury (AKI) is a sudden kidney dysfunction caused by aberrant reactive oxygen species (ROS) metabolism that results in high clinical mortality. The rapid development of ROS scavengers provides new opportunities for AKI treatment. Herein, the use of hydrogen‐terminated germanene (H‐germanene) nanosheets is reported as an antioxidative defense nanoplatform against AKI in mice. The simulation results show that 2D H‐germanene can effectively scavenge ROS through free radical adsorption and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Recently, Chen et al reported the design of 2D germanene nanosheets and their antioxidant application for AKI therapy. Hydrogen-terminated germanene (H-germanene) was synthesized through Ca layer deintercalation from the precursor Zintl-phase CaGe 2 crystals followed by delamination and ultrasonic treatment ( Chen et al, 2022 ). The hydrogenation strategy tuned the band gap of germanene, allowing H-germanene to be employed as an electron donor and thus serve as an antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al reported the design of 2D germanene nanosheets and their antioxidant application for AKI therapy. Hydrogen-terminated germanene (H-germanene) was synthesized through Ca layer deintercalation from the precursor Zintl-phase CaGe 2 crystals followed by delamination and ultrasonic treatment ( Chen et al, 2022 ). The hydrogenation strategy tuned the band gap of germanene, allowing H-germanene to be employed as an electron donor and thus serve as an antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…16g). 204,205 Simulations and experimental results revealed that 2D H-germanene could effectively scavenge ROS by radical adsorption and subsequent redox reactions. In vivo experiments showed that H-germanene largely attenuated apoptosis and renal damage in AKI mice (Fig.…”
Section: Anti-inflammationmentioning
confidence: 99%
“…Gold nanoclusters capped with NAC demonstrated improved antioxidative and anti-inflammatory effects compared with free NAC, achieving AKI reduction and reduced rodent mortality [19 ▪ ]. Several other substances that were traditionally known to act as antioxidants have been loaded into nanoparticles targeted to RTEC, successfully reducing oxidative stress in the injured kidney and mitigating kidney dysfunction [20 ▪ –26 ▪ ]. A promising strategy has been to co-load within nanocarriers both ROS scavengers along with drugs used to treat other damage mechanisms to further reduce inflammation [27 ▪▪ ] or intracellular calcium, which is believed itself to trigger multiple damage mechanisms [28 ▪▪ ].…”
Section: Acute Kidney Injurymentioning
confidence: 99%